SAT0016 Correlation of Carotid Intimal Plaque in SLE with Non-Traditional Serum Biomarkers. (10th June 2014) - Grönwall, C.; Reynolds, H.R.; Buyon, J.; Kim, J.; Goldberg, J.D.; Silverman, G.J.; Clancy, R.M.
Abstract : Background: Lupus patients have a strikingly increased risk of premature atherosclerosis and fatal cardiovascular events. This predisposition is neither fully accounted for by traditional cardiovascular (CV) risk factors nor SLE disease activity, thus supporting the need to identify biomarkers relevant to pathogenesis. Lower levels of protective natural IgM binding to oxidation-associated phosphorylcholine (PC) epitopes have been shown to correlate with CV events (myocardial infarction and stroke) in SLE. PC is present in oxidatively modified LDL, which plays a central role in atherogenesis, as well as on apoptotic cells. Moreover, IgM anti-PC enhances apoptotic cell clearance and induces anti-inflammatory pathways in innate immune cells. Objectives: To determine whether IgM anti-PC levels are associated with subclinical CV disease as assessed by carotid ultrasound. Methods: Sera were evaluated from 105 patients enrolled in a previously reported cross-sectional study in which carotid ultrasound was performed and adiponectin, soluble E-selectin and circulating endothelial cells were measured. The presence of plaque was defined as ≥50% increase over background intima media thickness (IMT) in any arterial segment. IgM antibody levels were assessed by ELISA. Statistical differences were assessed by Mann-Whitney test for univariate analysis of continuous variables and logistic regression multivariate analysis, with logarithmic transformation as appropriate. Step-wise logistic regression modeling was used for determining the best biomarker combination for prediction of plaque. Results: Of the studied patients, 44 had a carotid plaque. IgM anti-PC, and the ratio of IgM anti-PC/total IgM, were both significantly lower in patients with plaque compared to those without plaque (22±27 vs 39±47, p=0.004 and 0.47±0.5 vs 0.74±0.73, p=0.02, respectively). The ratio of IgM anti-PC/total IgM remained significantly lower in the plaque group, even after adjusting for age, total cholesterol and hypertension (p=0.005), which were found to be significant independent co-variables. As previously shown, the independent biomarkers, adiponectin and sE-selectin, were significantly elevated in the patients with plaque in univariate (p=0.01, p=0.005, respectively) and adjusted analysis (p=0.02, p=0.04, respectively). Notably, statistical modeling showed that combining the three tests (adiponectin, sE-selectin and IgM anti-PC/total IgM) improved the sensitivity (AIC=112, AUC=0.77) compared to each of the tests alone (AIC=142-133, AUC=0.66-0.67) or using only adiponectin with sE-selectin (AIC=123, AUC=0.73). Conclusions: The study confirms and extends the utility of measuring IgM anti-PC as a biomarker for CV disease in SLE, both with respect to established events as well as subclinical disease. The contribution of endothelial markers supports a pathogenic role for endothelial stress that coupled to impaired apoptotic cell clearance, associated with reduction in natural protective autoantibodies, may significantly promote lupus-associated atherogenesis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4322